2012
DOI: 10.4269/ajtmh.2012.12-0020
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Angiopoietin-1 and Angiopoetin-2 in Severe Dengue and Relationship with Thrombocytopenia, Endothelial Activation, and Vascular Stability

Abstract: Abstract. The pathogenesis of plasma leakage during dengue hemorrhagic fever/dengue shock syndrome (DHF/ DSS) is largely unknown. Angiopoietins are key regulators of vascular integrity: Angiopoietin-1 is stored in platelets and maintains vascular integrity, and endothelium-derived angiopoietin-2 promotes vascular leakage. We determined angiopoietin-1 and angiopoietin-2 levels in a cohort of children in Indonesia with DHF/DSS and related them to plasma leakage markers. Patients with DHF/DSS had reduced angiopoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 31 publications
3
63
0
2
Order By: Relevance
“…7 They commented this finding as an Ang/Tie imbalance and inducing the plasma leakage. 36 Our results supports this statement.…”
Section: Discussionsupporting
confidence: 94%
“…7 They commented this finding as an Ang/Tie imbalance and inducing the plasma leakage. 36 Our results supports this statement.…”
Section: Discussionsupporting
confidence: 94%
“…We previously reported that Ang-1 levels are also lower in dengue infection. 31 Plasma Ang-1 acts through the Tie-2 receptor, which is not expressed on post-capillary venules. 32 These venules are an important site for plasma leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DHF/DSS had reduced angiopoietin-1 and increased angiopoietin-2 plasma levels on the day of admission when compared with levels at discharge and in healthy controls. There was an inverse correlation between angiopoietin-1 and markers of plasma leakage and a positive correlation between angiopoietin-2 and markers of plasma leakage [10].…”
Section: Angiopoietinsmentioning
confidence: 97%
“…The existing laboratory tests to monitor abnormal host response [10][11][12] are complex, costly and require sophisticated laboratory infrastructure and trained personnel. Researchers should standardize 1-2 step in vitro assays which can be carried out in non-academic, non-research health centres.…”
Section: Point-of-care Assays Of Abnormal Host Factors In Denv Infectmentioning
confidence: 99%